Konsep Nilai-Nilai Keislaman dalam Kawruh Pamomong Ki Ageng Suryomentaram pada Aplikasi Pembelajaran Agama Islam di Sekolah - Nur Yaqin (Syntax Idea)
The rapid progress and human civilization has resulted in increasingly dimming Islamic values ​​and even starting to disappear from the existing vortex. This results in the dimming of Islamic values ​​and Islamic religious education and learning including the dimming of the attitude of religious and social responsibility from individuals and society, including the responsibility for children's Islamic education which has begun to nail and display in western education however, the form of reduced responsibility responsibility or trust include, such as reduced obedience to orders to carry out religious obligations, indifference to religious education in children, disregard for ethical and moral values ​​and diminished sense of empathy for people who are less affluent. This research is a research on the analysis of the concept of the content of Islamic values ​​in Ki Ageng Suryomentaram's kawruh pamomong in the application of Islamic religious learning. The purpose of describing the Islamic values ​​of the ancient text of kawruh pammong Ki Ageng Suryomentaram The object of study is the ancient manuscripts of Ki Ageng Suryomentaram. This type of research is qualitative research with a literature study model. The results of the study explain that local wisdom also has grain values ​​that can be used as speech and limitations in carrying out daily life. Results, The value points of kawruh pammong can be implemented in learning including several values ​​(1) exemplary; (2) habituation; and (3) question and answer. In conclusion, the application of Islamic values ​​as a benchmark or benchmark in applying belief to the understanding of the values ​​taught in the form of monotheism and morals. These values ​​can be applied and practiced in everyday life by believing in Islam as a reference material for its adherents.